Unlocking the English legal system - Frost, Tom (Lecturer in Law); Huxley-Binns, Rebecca; Martin, Jacqueline, 1945-; Mithani, Shaneez (Abingdon, Oxon ; London : Routledge, 2022)
"Unlocking the English Legal System will help you grasp the main concepts of the legal system in England and Wales with ease. Containing accessible explanations in clear and precise terms that are easy to understand, it provides an excellent foundation for learning and revising. This new edition offers a brand-new chapter on 'Ethics and Law' which details the duties and responsibilities of lawyers and introduces law students to the kinds of ethical dilemmas that they may encounter when they are lawyers. The up-to-date ongoing debates surrounding UK law are discussed, such as the impact Brexit and the coronavirus pandemic has and continues to have upon the English Legal System. Further detail on the devolution settlements in Northern Ireland, Scotland and Wales is provided as well as looking at the question of Scottish independence. Learn how to read cases and statutes, about career skills and interview preparation, and further information on how the new Solicitors Qualifying Examination (SQE) will operate and the reaction it's received from Law Schools. There is also focus on the impact of racism in the criminal justice system, the new Sentencing Code introduced in 2020, and how technology is changing the way the English Legal System operates. The books in the Unlocking the Law Series get straight to the point and offer clear and concise coverage of the law, broken-down into bite-size sections with regular recaps to boost your confidence. They provide complete coverage of both core and popular optional law modules, presented in an innovative, visual format"--
The sources of law -- The English legal system and European law -- The doctrine of judicial precedent -- Statutory interpretation -- Legal reasoning -- Civil courts -- Alternative dispute resolution -- Criminal courts and procedure -- Sentencing -- Appeals -- Funding -- Juries -- Lay magistrates -- The legal professions -- The judiciary -- Legal skills and examination preparation -- Ethics and law.
Includes bibliographical references and index.
Keywords: Law -- England